2008
DOI: 10.1002/per.682
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism predicts reactions to cues of social inclusion

Abstract: In the current paper, we hypothesized that people who are high in neuroticism (N) share a motivational predisposition to react vigilantly to threatening cues, most of which tend to be social in humans. In three studies, support for this prediction was found: based on cross-sectional and diary data, it was found that the self-esteem (SE) of individuals high in N decreases more in response to perceptions of relationship conflict and low relationship quality than that of emotionally stable ones. In a study of peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 63 publications
(75 reference statements)
4
90
1
1
Order By: Relevance
“…Higher neuroticism was associated with stronger appraisal-emotion associations, confirming that, for example, a more neurotic person reacts to unfair events with more anger than a less neurotic person. In a similar vein, Denissen & Penke (2008) found that the relation between poor relationship quality and low self-esteem was stronger for people high on neuroticism. Wasylkiw and colleagues investigated whether neuroticism moderated the effect on depression of ideal self-discrepancy, an aversive state in which one is failing to live up to one’s aspirations (Wasylkiw et al 2010).…”
Section: Negative Emotionalitymentioning
confidence: 76%
“…Higher neuroticism was associated with stronger appraisal-emotion associations, confirming that, for example, a more neurotic person reacts to unfair events with more anger than a less neurotic person. In a similar vein, Denissen & Penke (2008) found that the relation between poor relationship quality and low self-esteem was stronger for people high on neuroticism. Wasylkiw and colleagues investigated whether neuroticism moderated the effect on depression of ideal self-discrepancy, an aversive state in which one is failing to live up to one’s aspirations (Wasylkiw et al 2010).…”
Section: Negative Emotionalitymentioning
confidence: 76%
“…Neurotic people are typically insecure, irritable, easily disturbed, and lacking in self-confidence. They are generally impulsive and have been observed to undermine the social fabric of teams (Denissen & Penke, 2008;Rothmann & Coetzer, 2003). People exhibiting high levels of neuroticism are prone to irrational thought, impulsive behaviour, and applying poor coping strategies in stressful situations (Rothmann & Coetzer, 2003).…”
Section: Personality Traitsmentioning
confidence: 99%
“…Those who have high selfacceptance are less likely to be affected by negative life circumstances (Chamberlain and Haaga 2001), which contributes to emotional stability. Neuroticism has been associated in many studies with decreased marital and couple relationship satisfaction (see Malouff et al 2010 for meta-analysis) and an increased reactivity to social exclusion (Denissen and Penke 2008). From an attachment perspective, emotional stability is linked to optimal care from caregivers because as parents provide a stable and responsive environment, children develop an internal working model of the world as safe (Bowlby 1988).…”
Section: Emotional Stabilitymentioning
confidence: 98%